2006
DOI: 10.1159/000094623
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief after Pterygium Surgery with Viscous Lidocaine

Abstract: Purpose:The aim of the current study is to investigate the efficacy of lidocaine 2% gel for the control of pain experienced after pterygium surgery. Methods: We conducted a prospective, randomized clinical trial on 45 eyes of 45 patients who underwent pterygium surgery. The patients were randomized into 2 groups. Group 1 was provided with topical 2% lidocaine gel and group 2 with artificial tear gel. The primary outcome of interest was the pain experienced at the 4th, 7th and 10th postoperative hours. Corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Five studies describe 242 participants (256 eyes) with post-surgical corneal defects, four from photorefractive keratectomy (PRK) 34 , 35 , 37 , 39 and one from pterygium surgery. 36 Overall, the median study length is 7 days (IQR, 7–14 days) with a median of 11 days (IQR, 7–18 days) for post-trauma trials and 7 days (IQR, 3–7 days) for post-surgical trials. Overall, the median treatment duration is 24 hours (IQR, 24–168 hours) with a median of 36 hours (IQR, 24–78 hours) for post-trauma trials and 24 hours (IQR, 24–168 hours) for post-surgical trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies describe 242 participants (256 eyes) with post-surgical corneal defects, four from photorefractive keratectomy (PRK) 34 , 35 , 37 , 39 and one from pterygium surgery. 36 Overall, the median study length is 7 days (IQR, 7–14 days) with a median of 11 days (IQR, 7–18 days) for post-trauma trials and 7 days (IQR, 3–7 days) for post-surgical trials. Overall, the median treatment duration is 24 hours (IQR, 24–168 hours) with a median of 36 hours (IQR, 24–78 hours) for post-trauma trials and 24 hours (IQR, 24–168 hours) for post-surgical trials.…”
Section: Resultsmentioning
confidence: 99%
“…The following topical anesthetics are compared with placebo (Table 1): tetracaine 1% (2 RCTs), 23 , 39 0.5% (1 RCT), 22 and 0.4% (1 RCT); 40 proparacaine 0.05% (3 RCTs); 34 , 35 , 38 and lidocaine 2% (1 RCT). 36 One multi-arm trial compares proparacaine 0.05% and proparacaine 0.05% with topical diclofenac 0.1% against placebo. 35 One trial has an NSAID active control (diclofenac 0.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Another study investigated the use of topical lidocaine gel immediately after surgery and concluded that it was effective in controlling pain. 16 However, in their methodology, the patient had to wait 1 hour in the recovery room and then receive 1 drop of lidocaine gel each hour for the following 3 hours. In most clinical practices, this is not feasible because of time and structure logistics.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several studies attempt to demonstrate the efficacy of different strategies in reducing pain after surgery, such as topical lidocaine 2% gel, cyclopentolate, nonsteroidal antiinflammatory drugs, bandage contact lenses, and temporary occlusion. [13][14][15][16][17] Despite significant pain reduction, these strategies have drawbacks, primarily related to the increased cost of postoperative care and the risk of adverse events.…”
mentioning
confidence: 99%
“…In 2018, Prat et al compared therapeutic contact lenses and tight bandage patching for pain management and found that therapeutic contact lenses resulted in more discomfort, pain and decreased quality of sleep within the first 24 hours post pterygium surgery but that inconvenience of the bandaging limited the use of this method [11]. Oksuz and Tamer found that lidocaine 2% gel produced a statistically significant reduction in pain scores post operatively but also in an increase in mean corneal re-epithelization time from 34.36+/-10.00h in the control group to 37.56 +/-10.00h [12]. A small study of 80 participants found the use of topical cyclopentolate on post-operative pain post pterygium surgery has therapeutic potential, reducing pain scores significantly for the first 72 hours compared to the control group [13].…”
Section: Introductionmentioning
confidence: 99%